Unified model of shear modulus degradation curves in sand of guayuriba river (2014)
The purpose of this paper is to analyze the applicability of two unified model of shear modulus degradation curves in the sand of Guayuriba River (Department of Meta, Colombia). To achieve the objective, it was performed acyclic triaxial tests with controlled strain, by varying the confining pressure, the particle size and the compaction degree of the material. The outcome were the modulus degradation curves, which were compared against the model proposed by Ishibashi and Zhang, and the model proposed by Santos and Gomes Correia, showing that the behavior of these materials fit better to the second one.